Online Games Addiction and the Decline in Sleep Quality of College Student Gamers in the Online Game Communities in Surabaya, Indonesia - Kharisma, Andhika Cahya; Fitryasari, Rizki; Rahmawati, Praba Diyan (International Journal of Psychosocial Rehabilitation, 2020)
Addiction to online games in college students can lead to problems meeting basic needs for gamers such as eating, sleeping, and resting. This study aimed to analyze the relationship between online game addiction and sleep quality. The study design was descriptive analytic with a cross-sectional approach. The study population was college student gamers in the online gaming community in Surabaya. The sample of 111 respondents were obtained using a total sampling technique. The research instrument used online game addiction questionnaires and the Pittsburgh Sleep Quality Index (PSQI). The data obtained were then analyzed using the Spearman Rho test with level of significance p < 0.05. The results showed that the higher level of online game addiction, the lower the sleep quality of college student gamers in the online gaming community (p= 0,000; r= -0,751). Game addiction experienced by online gaming college students has a physical impact, especially the sensory system of the body’s sense of sight which causes the effects of fatigue that lead to difficulty in falling asleep and achieving good quality of sleep. College student gamers can manage their free time for playing online games so they don’t develop into addictions and therefore they can have a good quality of sleep.